2018
DOI: 10.1016/j.freeradbiomed.2018.04.561
|View full text |Cite
|
Sign up to set email alerts
|

Mapping three guanine oxidation products along DNA following exposure to three types of reactive oxygen species

Abstract: Reactive oxygen and nitrogen species generated during respiration, inflammation, and immune response can damage cellular DNA, contributing to aging, cancer, and neurodegeneration. The ability of oxidized DNA bases to interfere with DNA replication and transcription is strongly influenced by their chemical structures and locations within the genome. In the present work, we examined the influence of local DNA sequence context, DNA secondary structure, and oxidant identity on the efficiency and the chemistry of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 108 publications
1
20
0
Order By: Relevance
“…Not only do we see a significantly reduced depletion in high irradiance DNA-PAINT microscopy (I0=0.2 kW/cm2) (Figure 2 and Figure 3), but also in low irradiance SI-FCS measurements (I0=0.018 kW/cm2), we observed a close to zero depletion rate (Figure 4c,d and Table 2). The importance of ROS for photo-induced damages following fluorescence excitation has been studied not only in the context of fluorescence photo-bleaching [18,19,22,27,28,29], but also photo-toxicity [30,31] and in particular DNA damage [32,33,47]. ROS have also been shown to contribute to photo-induced unbinding of proteins [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Not only do we see a significantly reduced depletion in high irradiance DNA-PAINT microscopy (I0=0.2 kW/cm2) (Figure 2 and Figure 3), but also in low irradiance SI-FCS measurements (I0=0.018 kW/cm2), we observed a close to zero depletion rate (Figure 4c,d and Table 2). The importance of ROS for photo-induced damages following fluorescence excitation has been studied not only in the context of fluorescence photo-bleaching [18,19,22,27,28,29], but also photo-toxicity [30,31] and in particular DNA damage [32,33,47]. ROS have also been shown to contribute to photo-induced unbinding of proteins [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Different ROS, most prominently singlet oxygen and superoxide radicals, are supposedly formed from excited fluorescent states [29,54]. The likelihood and type of induced damage is reported to be sequence dependent and enriched at duplex ends [33]. Previous studies suggest that guanine is preferentially damaged, due to its lowest redox potential among the DNA bases [55,56,57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cleavage induced by the nanoparticles was studied in the pBR322 plasmid in the presence of Ag NPs via electrophoresis [168]. The results showed that guanine is the most affected nucleobase due to its low redox potential, and its oxidation produces a wide variety of modifications that ultimately affect DNA function ( Figure 7) [169]. NPs can not only affect bacteria but also other complex multicellular organisms through the induced genetic damage [170].…”
Section: Proteins and Dnamentioning
confidence: 99%